Situation Report: Hungary, 1 March 1977 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Changes in the Hungarian National Economic Structure (III) Writer Istvan Csurka Speaks Out on Sensitive Issues Uj Ember on the Spirit of Helsinki Public Discussion on the Decline of Tourism Last Year's Shortfall Places Heavy Burden on Agriculture